2015
DOI: 10.1177/1069397115594355
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Love’s Universal Attributes

Abstract: There are no cognitive studies of love conducted in an Asian culture. Our study is the first to probe the cognitive qualities that urban Chinese youth associate with what it means to be in love. To this end, we build on de Munck et al.'s pioneering studies in two European cultures (Russia, Lithuanian) and in the United States. Expanding on their study, we used a similar questionnaire that also includes additional questions designed to probe the youth of urban China's perception and understanding of romantic lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
2
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 25 publications
6
38
2
1
Order By: Relevance
“…The following six statements were used to measure the romantic ATL: (a) The fact that I do not like his or her friends does not reduce my love for him or her; (b) no matter what happens, as long as I love him or her, we will get married; (c) my world would become entirely miserable if I broke up with my partner; (d) love is the most important thing, and nothing else is worth considering; (e) my life is meaningless if I cannot stay together with the one I love; and (f) my love cannot be shaken by dissenting opinions from my parents, relatives, and friends. These items are consistent with previous work gauging ATL (e.g., Hopkins, ; Knox & Sporakowski, ), and studies have shown that they are reliable and valid in the Chinese context (Jankowiak, Shen, Yao, Wang, & Volsche, ; Shao & Hu, ; J. Wang, ). Cronbach's alpha for these items are shown in Appendix S1.…”
Section: Empirical Strategiessupporting
confidence: 90%
“…The following six statements were used to measure the romantic ATL: (a) The fact that I do not like his or her friends does not reduce my love for him or her; (b) no matter what happens, as long as I love him or her, we will get married; (c) my world would become entirely miserable if I broke up with my partner; (d) love is the most important thing, and nothing else is worth considering; (e) my life is meaningless if I cannot stay together with the one I love; and (f) my love cannot be shaken by dissenting opinions from my parents, relatives, and friends. These items are consistent with previous work gauging ATL (e.g., Hopkins, ; Knox & Sporakowski, ), and studies have shown that they are reliable and valid in the Chinese context (Jankowiak, Shen, Yao, Wang, & Volsche, ; Shao & Hu, ; J. Wang, ). Cronbach's alpha for these items are shown in Appendix S1.…”
Section: Empirical Strategiessupporting
confidence: 90%
“…In contrast to descriptive research into universal characteristics of love which does not identify differences between representatives of individualistic and collectivistic cultures (Yildirm et al, 2014;Jankowiak et al, 2015), in this study we view the distinctions in concepts of love as deeply implanted, quite similarly, in the roots of the collectivist cultures studied and serve as a distinguishable cultural code (Espín, 2013). The core zone of love for Brazilians is honesty, for Russians -suffering, and for Central Africans -tenderness.…”
Section: Discussionmentioning
confidence: 73%
“…However, the representation of love among Chinese young people (as representatives of a typical collective culture) showed no differences between them and their American counterparts (who are representatives of a typical individualistic culture). The two groups shared similar ideas of love, which included "altruism, " "intrusive thinking, " "self-actualization, " "emotional fulfillment, " "sexual attraction, biology" (Jankowiak, Shen, Yao, Wang, & Volsche, 2015). The adaptation of the questionnaire "The passionate love scale" used by Yildirm, Hablemitoglu, and Barnett (2014) with Turkish students, also revealed that love is understood by the Turkish students in the same way as in an individualistic culture.…”
mentioning
confidence: 89%
“…Further validating the cross-cultural salience of the survey, Jankowiak et al (2015) provided the first dataset from an Asian culture. Reporting on a sample from Fudan University, Shanghai, the authors found that the youth of urban China hold many of the same perceptions of romantic love as do their Western counterparts from the previous studies.…”
Section: Introductionmentioning
confidence: 99%